Lei Nacional de Adoção e o acolhimento institucional: o ponto de vista dos psicólogos e assistentes sociais - Silva, Milena Leite (2012)
The dynamics of the youth shelters and the repercutions to children and adolescents after being in such institutions have been increasingly studied. In 2009, a new Law was created, proposing renewal of the existing practices in such places, which have already been changed since the Children and Adolescents Statute. From such starting point, the research which originates the following thesis aimed to know how psychologists and social workers, employees of technical teams of youth shelters, perceive some of the changes of the new National Adoption Law (Law 12010/2009). It is a qualitative, descriptive and exploratory study, carried out with eight professionals, four psychologists and four social workers, the total number of professionals of youth shelters in the city where the research was carried out. Semi-structured interviews were carried out with openended questions, which were analyzed through content analysis. Results are presented in three articles. In the first of them, the aim is to understand the changes that the new Law may bring to the relationship among families and youth shelters. The interviewed professionals show consistent knowledge about the new Law and highlight good initiatives concerning the work towards families of children and adolescents in such situation. However, some stigmatizing discourses related to the families are identified. The second article reflects about the understanding of the interviewed professionals about the changes in their work, after the new Law. Such study points out that youth shelters are understood by participants as places that combine the old and new features of the institutionalization history, which demonstrates that there are ambivalences and practices that need to be overcome. Yet, a movement generated by the new National Adoption Law regarding the practice of interviewed professionals is clear, demanding more agility and speed in the development of the work. The third article concerns family reinsertion, problematizing such practice that is encouraged by the new Law. Results evidence that professionals exhaust the possiblities of searching for the family, and only after, try to guarantee family and community living, counting on the extensive family, which presents peculiarities, according to the participants. In order to promote reinsertion, listening to the family has been valued, guiding the actions. Results also focus the facilities and the difficulties during the resinsertions process, the practices used to promote it and the farewell from the institution. The reality portrayed in such articles shows that it is not possible to infer general characteristics about the situation. However, there seems to be a movement of change happening, as concerns the total number of participants, showing the advance or the stagnation evidenced in their discourses do not refer to the lack of knowledge about the new law, but to the closeness or the distance of the prevailing practices throughout the years.